2022
DOI: 10.1364/boe.443880
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of diffuse reflectance spectra analysis by inverse adding doubling algorithm

Abstract: Analysing diffuse reflectance spectra to extract properties of biological tissue requires modelling of light transport within the tissue, considering its absorption, scattering, and geometrical properties. Due to the layered skin structure, skin tissue models are often divided into multiple layers with their associated optical properties. Typically, in the analysis, some model parameters defining these propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Although we have no ground truth values for estimated tissue parameters, based on our previous observations for simulated reflectance skin spectra, the mean values of fitted parameters are within AE1 STD from the actual values. We also demonstrated that the correlation between the estimated parameters depends on the selection of fixed parameters [57]. In the present study, f m and d e exhibited the highest negative correlation (Pearson correlation coefficient was p 12 ¼ À0:7538), meaning a decrease in epidermal thickness yields a higher melanin volume fraction.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Although we have no ground truth values for estimated tissue parameters, based on our previous observations for simulated reflectance skin spectra, the mean values of fitted parameters are within AE1 STD from the actual values. We also demonstrated that the correlation between the estimated parameters depends on the selection of fixed parameters [57]. In the present study, f m and d e exhibited the highest negative correlation (Pearson correlation coefficient was p 12 ¼ À0:7538), meaning a decrease in epidermal thickness yields a higher melanin volume fraction.…”
Section: Discussionsupporting
confidence: 60%
“…The fit results also show a good agreement between the measured and fitted spectra, suggesting that the IAD algorithm is accurate and robust in extracting the tissue parameters. However, our recent publication [57] showed that different sets of model parameters could yield precisely the same reflectance spectra, meaning there is already some intrinsic uncertainty in parameter estimation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for hyperspectral image analysis, a GPU-accelerated inverse adding-doubling (IAD) algorithm was developed in MATLAB R2020b (Mathworks, Natick, MA) for fast and accurate light propagation simulation in layered turbid media 5 . Briefly, we utilized a two-layer murine skin model consisting of an upper layer (epidermis) and a semi-infinite lower layer (dermis) with 11 model parameters describing tissue physiology (e.g., melanin, hemoglobin) and morphology (e.g., scattering power) 7 . The measured reflectance spectra were fitted using the Levenberg-Marquardt (LM) algorithm adopted for GPU to extract all model parameters.…”
Section: Image Processing and Analysis By The Inverse Adding-doubling...mentioning
confidence: 99%